Neonatal Pellagra - Hiroki Kitaoka; Satsuki Kakiuchi (Clinical Case Reports)
ABSTRACT When infants develop an intractable rash, even in developed countries, considering the possibility of malnutrition and taking the mother's dietary history are important. The nutritional status of preterm infants after fortification of the mother's milk is discontinued should be carefully monitored.